2005
DOI: 10.1111/j.0022-202x.2005.23754.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of 0.1% Tacrolimus Ointment After First and Repeated Application to Adults with Moderate to Severe Atopic Dermatitis

Abstract: The systemic exposure to tacrolimus after first and repeated application of 0.1% tacrolimus ointment was investigated in 32 adults with moderate to severe atopic dermatitis. Patients were allocated to treatment groups according to the size of the affected area to be treated: Group 13000 cm(2)6000 cm(2) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 10 publications
6
54
0
3
Order By: Relevance
“…4,5 Considering that even clinically normal-appearing skin in patients with AD is immunologically abnormal, 6 we hypothesized that maintenance therapy with tacrolimus ointment, a topical, nonsteroidal, calcineurin inhibitor, applied to previously involved skin might help to prevent relapse in these patients. Clinical and pharmacokinetic studies in patients with AD have shown that tacrolimus ointment is associated with minimal systemic absorption and no evidence of accumulation, [7][8][9][10][11][12] and long-term (6 months-4 years) safety and efficacy have been demonstrated in more than 10,000 patients. [13][14][15][16][17] The current prescribing information for both tacrolimus ointment and pimecrolimus cream (as revised in January 2006) states that continuous longterm use of topical calcineurin inhibitors should be avoided, and application should be limited to areas of involvement with AD.…”
mentioning
confidence: 99%
“…4,5 Considering that even clinically normal-appearing skin in patients with AD is immunologically abnormal, 6 we hypothesized that maintenance therapy with tacrolimus ointment, a topical, nonsteroidal, calcineurin inhibitor, applied to previously involved skin might help to prevent relapse in these patients. Clinical and pharmacokinetic studies in patients with AD have shown that tacrolimus ointment is associated with minimal systemic absorption and no evidence of accumulation, [7][8][9][10][11][12] and long-term (6 months-4 years) safety and efficacy have been demonstrated in more than 10,000 patients. [13][14][15][16][17] The current prescribing information for both tacrolimus ointment and pimecrolimus cream (as revised in January 2006) states that continuous longterm use of topical calcineurin inhibitors should be avoided, and application should be limited to areas of involvement with AD.…”
mentioning
confidence: 99%
“…Rubins et al [7] investigated pharmacokinetic parameters of topical tacrolimus. There was a trend for systemic exposure to increase proportionally as the size of the treatment area increased, but exposure was still substantially lower than for transplant patients.…”
mentioning
confidence: 99%
“…Topical applications of tacrolimus ointment result in minimal systemic absorption, do not cause a decrease in collagen synthesis or skin thickness, and have not been associated with limiting adverse events thus far. [16][17][18][19][20][21] Tacrolimus ointment (0.03% and 0.1%) has been clinically shown to reduce the extent, severity, and symptoms of moderate to severe AD in children as young as 2 years of age and to be safe and effective for long-term use for up to 4 years. [22][23][24][25][26][27] However, it has not been evaluated for treatment of mild to moderate cases.…”
mentioning
confidence: 99%